Liver Injury and Elevated Levels of Interleukins, Interleukin-2 Receptor, and Interleukin-6 Predict the Severity in Patients With COVID-19 - Kuan Luo; Kuan Luo; Kuan Luo; Yongfeng Chen; Yongfeng Chen; Junjie Yang; Quan Tao; Quan Tao; Min Luo; Min Luo; Min Luo (Frontiers Media S.A., 2021)
The novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread worldwide, and the WHO declared it a pandemic on March 11, 2020. Clinical characteristics and epidemiology features of patients infected with SARS-CoV-2 have been explored in the previous study. However, little is known about the combinative association of liver dysfunction and abnormal interleukins (ILs) in severe patients with COVID-19. This study was designed to estimate whether liver dysfunction and abnormal ILs could predict the severity of COVID-19. This study integrated liver function data and ILs data in patients with COVID-19 and found that liver injury and two ILs, interleukin-2 receptor (IL-2R) and interleukin-6 (IL-6), were closely related to the prognosis of patients with COVID-19. This study may give more exact information to clinicians about the prognosis of patients with COVID-19. In addition, this correlational study between liver disorder and ILs may provide a new vision to diagnosis and treatment in patients.